Impacto del cambio climático en la adaptación de prácticas agrícolas tradicionales en el cultivo de maíz (Zea mays L). - Chileno Guano, Vanessa Tatiana (2025)
Corn is one of the most important crops in agriculture worldwide, however, due to climatic variations, its production has been affected. The general objective of this research was to describe the climatic factors that influence the adaptation of traditional agricultural practices in corn cultivation, in order to provide possible solutions. To carry out this research, updated information was collected from scientific articles, websites, Google Scholar and virtual libraries, which allowed obtaining opinions and ideas from various authors on this subject. The research was developed as a non-experimental work of a bibliographic nature, using synthesis, analysis and summary of the information collected. The impact of climate change on corn cultivation was addressed, considering that traditional practices such as burning waste, inappropriate use of pesticides and synthetic fertilizers, monoculture and conventional tillage directly affect climate change, so it is necessary to implement mitigation and adaptation strategies. The adoption of sustainable agricultural practices in the face of climate change has proven to be essential not only for viable production, but also for reducing the effects of climate change. The implementation of strategies to mitigate the effects of climate change includes variety selection, sustainable soil management, agroforestry, among others. It is also important to promote the education and training of farmers on these sustainable and climate-resilient practices in order to safeguard agricultural production and food security.